Secrets of the PlayStation Portable - Durham, Joel (Peachpit Press, 2006)
With over 13 million shipped, the Sony PlayStation Portable, or PSP, is one of the fastest selling game consoles in history. In this essential guide, gaming expert Joel Durham, Jr. shows readers how to get the most out of this revolutionary handheld game console. After an initial tour around the interface, Joel will introduce the readers to the multimedia possibilities of the PSP, including gaming, movie playback, organizing and playing music, organizing and displaying photographs, and web surfing and RSS. In addition he will walk readers through how to use the device on a network, how to get the most life from the battery, how to pick a headset, how to set up a WLAN and more.